Sensorineural hearing loss in a child with congenital hypothyroidism receiving thyroid hormone replacement therapy - Semiramis Zizlavsky; Tri Handayani; Ronny Suwento; Eka Dwi Safitri; Tri Juda Airlangga (PERHATI-KL, 2022)
ABSTRACTBackground: Congenital hypothyroidism remains as one of the most common causes of hearing loss in children, considering that thyroid hormone plays an essential role in the development and maturation of auditory organs. Purpose: To report a case of hearing loss in a child with congenital hypothyroidism who had received thyroid hormone replacement therapy. Case report: Presenting a 3-year-old boy with congenital hypothyroidism, growth and developmental delays, and a very severe bilateral sensorineural hearing loss. He was diagnosed at 6 months old, and even after subsequent therapies, the hearing impairment of the child remained profound. Clinical question: Could thyroid hormone replacement therapy improve the prognosis of hearing function in congenital hypothyroid patients accompanied by sensorineural hearing loss? Review method: Literature review through database PubMed, ProQuest, EBSCO, EBSCOhost and Embase, using keywords: “congenital hypothyroidism”, “hearing loss”, and “thyroid hormone replacement therapy”. Result: Screening on 1088 articles found no studies that were relevant with the clinical question and inclusion criteria. Conclusion: This report supported the evidence on the effects of congenital hypothyroidism on hearing loss, and the importance of early diagnosis and prompt treatment in congenital hypothyroid children. A missed diagnosis of congenital hypothyroidism in neonates may result in unfavorable effects on the child’s growth and development. Further studies are needed to assess the improvement of hearing function in congenital hypothyroid patients accompanied by sensorineural hearing loss that received thyroid hormone replacement therapy. ABSTRAKLatar belakang: Hipotiroidisme kongenital merupakan salah satu penyebab paling umum gangguan pendengaran pada anak-anak, terutama mengingat hormon tiroid berperan penting dalam perkembangan dan maturasi organ pendengaran. Tujuan: Melaporkan satu kasus gangguan pendengaran pada anak dengan hipotiroidisme kongenital yang menetap setelah terapi sulih hormon tiroid. Laporan kasus: Seorang anak laki-laki berusia 3 tahun dengan hipotiroidisme kongenital yang mengalami keterlambatan pertumbuhan dan perkembangan, dan gangguan pendengaran tipe sensorineural bilateral derajat sangat berat. Pasien didiagnosis pada usia 6 bulan, dan walaupun setelah terapi, gangguan pendengaran pada anak tersebut menetap. Pertanyaan klinis: Apakah terapi sulih hormon tiroid mempengaruhi prognosis perbaikan fungsi pendengaran pada pasien hipotiroid kongenital yang disertai gangguan pendengaran sensorineural? Tinjauan literatur: Melalui database PubMed, ProQuest, EBSCO, EBSCOhost dan Embase, menggunakan kata kunci: “hipotiroidisme kongenital”, “gangguan pendengaran”, “terapi sulih hormon tiroid”. Hasil: Setelah skrining 1088 artikel, tidak ada penelitian yang sesuai dengan pertanyaan klinis dan kriteria inklusi. Kesimpulan: Laporan ini menambah bukti tentang efek hipotiroidisme kongenital pada gangguan pendengaran, serta pentingnya diagnosis dini dan pengobatan segera pada anak hipotiroid kongenital. Diagnosis hipotiroidisme kongenital yang tidak terdeteksi pada neonatus, dapat mengakibatkan efek buruk pada pertumbuhan dan perkembangan anak. Diperlukan penelitian lebih lanjut untuk menilai prognosis peningkatan fungsi pendengaran pada pasien hipotiroid kongenital dengan gangguan pendengaran sensorineural, yang mendapatkan terapi sulih hormon tiroid.